Teaching and Practicing Model Predictive Control. Issue 6 (2016) - Honc, Daniel; Sharma K., Rahul; Abraham, Anuj; Dušek, František; Pappa, Natarajan
Abstract: How to explain Model Predictive Control (MPC) to students? How to practise it? The paper deals with chain of actions involving teaching, practicing and laboratory application of MPC at University of Pardubice in Czech Republic and at Anna University in India. Individual steps are presented and discussed with examples from educational experience - e.g. modelling and identification, derivation of MPC controller, simulations and laboratory applications. Every phase has a key and weak point as well. Desired results is that students understand better the theoretical concepts and they are able to apply predictive controllers at least for laboratory processes. Derivations and MATLAB scripts are available online.